Promoted Rh nanocrystal-incorporated carbon sphere catalysts for higher alcohol synthesis. (1st April 2016) - Lim, Jemi; Park, Hae-Gu; Kim, Tae-Wan; Kim, Daegak; Ha, Kyoung-Su
Graphical abstract: Highlights: Carbon sphere supported Rh catalyst is suitable for higher alcohol synthesis. Selectivities towards butanol and propanol are greatly improved due to carbon sphere. FT-IR analysis indicates that modes of CO adsorption and band shift are essential. The other supports are compared such as alumina, silica, titania, and mesostructured carbon. Abstract: Biomass-derived saccharides were used to form a support for Rh-based catalytic nanocrystals for synthesizing higher alcohols such as ethanol, propanol, and butanol from synthesis gas. Using hydrothermal synthesis with the saccharide and metal precursors in one pot, Rh-based nanocrystals encapsulated in carbon spheres were successfully manufactured at elevated temperature and pressure. These types of catalysts were found to show a significantly higher selectivity for C3 and C4 alcohols as well as C2 oxygenates. Through comparative experiments, ordered mesoporous carbons were also found another good catalyst supports for higher alcohol synthesis. The size and morphology of carbon sphere supported Rh-based catalyst were examined by scanning electron microscopy, and each incorporated metal species was identified by elemental analysis. Transmission electron microscopy was used to investigate the size and size distribution of nanocrystals. More importantly, CO gas adsorption experiment with FT-IR spectrometer elucidated that the carbon supported Rh-based catalysts in this study were found to increase the amount of active intermediates adsorbed on the catalyst surface.